Transforming Healthcare through Entrepreneurial Innovations: An Institutional View - Wallin, Arto (International journal of e-services and mobile applications, 2017)
Although digitalization has profoundly changed the business logic in many industries, the healthcare sector still operates in many areas as in the pre-digital era. During recent years, humans have witnessed the rise of new digital health ventures, many of which have revolutionary ideas of how to transform business logics in the organizational fields of healthcare. However, in many cases the institutional arrangements of the field are so strong that new ventures face major challenges in breaking the institutional elements that prevent the introduction and diffusion of service innovations. This paper studies the cases of five companies that aim to transform specific niche areas in healthcare and how these entrepreneurs perceive the influence of institutional elements on their actions.